Giving up God : resurrecting a spirituality of love and wonder - Hayward, Sarah Henn (Lake Drive Books, 2023)
"Many of us are taught to believe that our only hope is in a supernatural, all-powerful, Christian God. Yet we wonder, is God really real? If we pursue our questions, what might we find? After three decades of embarking on mission trips, leading Bible studies, and participating in church leadership teams, Sarah Henn Hayward's spiritual identity was overturned when lived experience conflicted directly with handed-down religion. From traveling the world and meeting people of different faiths and backgrounds, making friends with amazing people who happened to be queer, to reading widely from books about science, psychology, and social justice, the veil created by concepts like hell, evolution, and Christian exclusivity was lifted in favor of an exploration of a stronger sense of self and a more expansive worldview." -- Back cover